Expression of CXCR4 on CD4+ T cells predicts body composition parameters in female adolescents with anorexia nervosa - Freff, Jana; Bröker, Lisa; Leite Dantas, Rafael; Schwarte, Kathrin; Bühlmeier, Judith; Kraft, Isabelle; Hinney, Anke; Buhlmann, Ulrike; Arolt, Volker; Dannlowski, Udo; Romer, Georg; Baune, Bernhard T.; et al. (Frontiers in Psychiatry, 2022)
Anorexia nervosa (AN) is a severe eating disorder characterized by excessive weight loss and lack of recognition of the seriousness of the current low body weight. Individuals with AN frequently exhibit an enhanced inflammatory state and altered blood levels of cytokines and chemokines. However, the expression of chemokine receptors in AN and the association with body composition parameters and treatment effects are still unknown. In this study, we examined the expression of CCR4, CCR6, CXCR3, and CXCR4 on peripheral blood T cells in female adolescents with AN before (T0, n = 24) and after 6 weeks of multimodal therapy (T1, n = 20). We also investigated their value to predict body mass index (BMI) and fat mass index (FMI) at baseline. Using multi-parameter flow cytometry, we found increased expression of CCR4, CXCR3, and CXCR4, but not CCR6, on CD4+ T cells in AN at T0, when compared to healthy controls (HC, n = 20). At T1, CXCR3 and CXCR4 expression decreased in AN. We found a close link between CCR4, CCR6, and CXCR4 expression and the adolescent mental health status in the study cohort as determined by the Strengths & Difficulties Questionnaire (SDQ). Specifically, CXCR4 expression correlated positively with emotional symptoms and peer relationship problems, as well as with the total sum score of the SDQ. In addition, CXCR4 expression on CD4+ T cells was a significant predictor of BMI and FMI in female adolescents. Our findings that CXCR4 expression on T cells is altered in adolescents with AN and predicts body composition parameters in adolescents suggest an impact of this chemokine receptor in the pathogenesis of AN.